PENGARUH PRODUK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN RESTAURANTYUGO DI GADING SERPONG: THE EFFECT OF PRODUCT, PRICE AND QUALITY OF SERVICE ON CUSTOMER SATISFACTION TYUGO RESTAURANT IN GADING SERPONG - Merry Meyghel Wensen; Leo Alexander Tambunan (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2022)
Price can be one reason for customers to decide to buy the goods or services they need. Because with a low price but getting the quality of goods that are in accordance with what they want, the customer will feel satisfied. Product quality is a very important part related to products that meet consumer desires or expectations. Customers in making their choices will definitely choose the one that suits their needs and desires that can make them feel satisfied and then decide to continue buying the product. A person's decision to buy one of them is influenced by an assessment of the quality of the product. The purpose of this study was to determine the effect of product, price and service quality on customer satisfaction at Yugo Restaurant in Gading Serpong. This research is a quantitative field research. The population in this study were all customers at Yugo Restaurant in Gading Serpong in the amount of 150 people, with a sample of 60 customers taken at random (random sampling). The data collection technique used a questionnaire and the data analysis technique used multiple linear regression analysis. The results showed that based on the results of multiple regression analysis on the fourth hypothesis test, namely that there is an effect of Product, Price and Service Quality together on customer satisfaction, it is known that the calculated F value is 755.461, and with a significance level (p-value), 0.000. This means that the value of Sig < value (0.000 < 0.05), it can be concluded that there is an effect of Product, Price and Service Quality together on customer satisfaction at Yugo Restaurant in Gading Serpong. The magnitude of the effect of the variable Product, Price and Service Quality simultaneously (together) on customer satisfaction is 97.6%.